Childbirth in women with intellectual disability: characteristics of their pregnancies and outcomes in an archived epidemiological dataset. (20th October 2014) - Goldacre, A. D.; Gray, R.; Goldacre, M. J.
Abstract Background Historically, many women with intellectual disability (ID) did not have children. However, a few decades ago it became more common for women with ID to give birth. Our aim was to compare the completed pregnancies of mothers with ID with other completed pregnancies in a large, defined population. Methods We used the archived dataset of the Oxford record linkage study from 1970 to 1989, which included a specialized dataset of all maternities in a population of 850 000 people. Results There were 245 007 births, of which 217 were to mothers with a record of ID. Mothers with a record of ID were more likely than others to give birth at a young age, were much more likely to be unmarried (42% compared with 9%) and to have smoked in the pregnancy (54% compared with 23%). Comparing babies born of mothers with ID and others, percentages with very low birth weight (<2000 g) were similar at 1.9 and 1.8%. There was no excess of babies who were low birth weight for gestational age. Babies born of mothers with ID were much less likely than others to be breastfed (respectively, 33 and 70%). There were no significant associations with presentation at delivery, Caesarean section or forceps delivery. The distribution of Apgar scores at 1 min after birth was similar in babies of mothers with ID and other babies. The sex ratio of the babies was normal. Combining stillbirths and infant deaths, rates per 1000 were 27.9 for babies of mothers with ID and 13.4 in other babies (borderline significant at P = 0.07). Conclusions Comparing pregnancies and outcomes of mothers with and without ID, there are some important differences, and some important similarities. It is possible, however, that there may be differences over time and between different places in the care and outcomes of pregnancies in mothers with ID. In the modern era, with electronic health records, it should be possible for maternity services, both locally and on a whole population basis, routinely to monitor the pregnancies, and their outcomes, of mothers with ID.